2021
DOI: 10.1002/onco.13721
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Characteristics, Treatment Patterns, Health Care Resource Use, and Costs of Patients with Diffuse Large B-Cell Lymphoma in the U.S

Abstract: Background Diffuse large B‐cell lymphoma (DLBCL) represents the most common subtype of non‐Hodgkin lymphoma in the U.S., but current real‐world data are limited. This study was conducted to describe real‐world characteristics, treatment patterns, health care resource utilization (HRU), and health care costs of patients with treated DLBCL in the U.S. Materials and Methods A retrospective study was conducted using the Optum Clinformatics Data Mart database (January 2013 to March 2018). Patients with an Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…While the treatment duration is very close to our findings, associated costs are much higher, especially in later lines of therapy. Another US study reported average annual costs of $137,156 across therapy lines for patients receiving treatment [17]. Another study concluded that average yearly costs for secondline patients were even higher, and stood at $210,488 [18].…”
Section: Discussionmentioning
confidence: 99%
“…While the treatment duration is very close to our findings, associated costs are much higher, especially in later lines of therapy. Another US study reported average annual costs of $137,156 across therapy lines for patients receiving treatment [17]. Another study concluded that average yearly costs for secondline patients were even higher, and stood at $210,488 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 4361 French patients alive at their last examination, 3317 were eligible for the survey, and 1671 (50.4%) participated with a median follow-up of 11 years (range, 5-22 years) after the initial treatment of their lymphoma. 19 The study was approved by French legal authorities, namely the Consultative Committee for Data Processing in Health Research and the National Commission on Informatics and Liberty (DR-204-252).…”
Section: Study Populationmentioning
confidence: 99%
“…Its evaluation is difficult because of the nature of the disease and its treatment variability; it is also difficult to compare the results of studies from different countries. [7][8][9][10][11][12][13][14][15][16][17][18][19] To our knowledge, no study has focused on the economic burden in NHL survivors (who have at least 5 years of follow-up after treatment initiation), even though this knowledge is essential. Most survivors are elderly with a potential risk of comorbidity development related to their age and the disease itself (persistent and/or long-term adverse events such as fatigue, relapse, and secondary or new primary cancer).…”
Section: Introductionmentioning
confidence: 99%
“…Although nearly 60% of patients achieve complete remission to 1L treatment, up to 50% could develop refractory or relapsed (R/R) disease, which carries a poor prognosis. 4,5 Though high-dose chemotherapy followed by autologous stem cell transplant (ASCT) is the recommended SOC for eligible patients in the 2L setting based on results from the pivotal PARMA study, real-world SOC in this setting remains less clearly defined. 6,7 The emergence of novel treatment strategies, such as chimeric antigen receptor T-cell (CAR-T) therapy in October 2017, polatuzumab in June 2019, and targeted agents, has provided additional treatment options for patients with R/R DLBCL, but their real-world uptake and outcomes remain poorly understood and quantified.…”
Section: Introductionmentioning
confidence: 99%